It's never too late to achieve financiel security... start today - "Cerexhe, Peter" (Crows Nest, 2007)
At some point in our lives most of us find we've lost part, or all of our motivation to arrange our personal finances. Some of us never had the motivation in the first place. A studied look at property, share market and your superannuation, and also avoiding the toll on relationships when we mess it up.
Keywords: "Financial, personal"